CATAPHOT OF ROAD BARRIER RAILING WITH INDEPENDENT SYSTEM OF ELECTRIC LIGHTING - V. I. Kapaev (Известия высших учебных заведений: Проблемы энергетики)
A signal light device construction of warning light indication was proposed for road barrier railing. It combines two working modes: passive - light reflective cat’s eye and active -light emitting one. The purpose of the proposal is the improvement of visual informative capacity along with minimal power consumption and as a result the increase of road traffic safety.